Improving English speaking skills through project-based learning (PjBL): A case study of computer assisted language learning (CALL) - Widyawati, Yogi; Siregar, Elitaria Bestri Agustina; Wardhani, Rika Novita (Politeknik Negeri Bali, 2024)
The mini research aims to assist students of 2nd semester at Electronic Department of PNJ to improve their English-speaking skills. Since the Project-Based Learning has been put into the curriculum, every subject must be connected to it. The study was conducted through the following stages: observation, coaching and action. It involved 44 students of the 2nd semester and a teacher as a facilitator. The students were asked to do final project based on Computer Assisted Language Learning (CALL). The results were mini videos which were upload in social media (YouTube). The impact of this activity was significant. Students’ score in speaking skills were improved 75%. It means that project based on CALL motivates students and “force” students to speak actively.